Lasing modes in ZnO nanowires coupled to planar metals - Repp, Daniel; Barreda, Angela; Vitale, Francesco; Staude, Isabelle; Peschel, Ulf; Ronning, Carsten; Pertsch, Thomas (Optics Express, 2023)
Semiconductor nanowire lasers can be subject to modifications of their lasing threshold resulting from a variation of their environment. A promising choice is to use metallic substrates to gain access to low-volume Surface-Plasmon-Polariton (SPP) modes. We introduce a simple, yet quantitatively precise model that can serve to describe mode competition in nanowire lasers on metallic substrates. We show that an aluminum substrate can decrease the lasing threshold for ZnO nanowire lasers while for a silver substrate, the threshold increases compared with a dielectric substrate. Generalizing from these findings, we make predictions describing the interaction between planar metals and semiconductor nanowires, which allow to guide future improvements of highly-integrated laser sources.
CRIS-Team Scopus Importer:2023-04-20